THE IMPACT OF HIV/AIDS ON SOCIAL ECONOMIC WELLBEING OF PEOPLE IN NORTHERN CITY DIVISION OF MBALE CITY - NEUMBE CAROLINE (My University, 2024)
ABSTRACT The study concentrated on the impact of HIV/AIDS on social economic wellbeing of people in Northern City Division of Mbale City. The study concentrated on three specific objectives of: To explore the factors contributing to HIV/AIDS infections among people in Northern City Division Mbale city, to examine the effects of HIV/AIDSD on socio-economic wellbeing of people of Northern City Division Mbale City and lastly to assess interventions of preventing HIV/AIDS infections so as to enhance socio-economic well-being of people in Northern City Division, Mbale City. The study used a descriptive research design and considered a sample size of 80 respondents. Findings concluded that culturally prescribed acts of sexual promiscuity lead to increase in HIV/AIDS findings also I concluded that Heterosexual contributes to HIV/AIDS, Findings concluded that provision of ARVs to reduce viral loads may act as a strategy to improve socio-economic wellbeing of affected people, that practice of bottle feeding may help to prevent Mother to-Child transmission can work as a prevent measure the spread of the infection and lastly, findings concluded that Increasing accessibility of use of protective condoms may work as a strategy to reduce the infection and improve on socio-economic well-being of people. The study recommended that: There should be more investments by different Governments in a number of strategies to ensure that HIV stigmatization is reduced in different communities and lastly that there is need for the to sensitize the community and people taking care of HIV affected people ensure that they are emotionally ok.